(untitled) (Bangladesh Journal of Pharmacology, 2016)
Y-box binding protein 1 (YB-1) is an imperative biomarker for the clinical out-come of cancer patients. An overexpression of YB-1 in cancerous and adjoining tissues is an indication of aggressiveness and advanced stages. In normal resting cells, YB-1 is localized in cytoplasm while in stress conditions like cancer, nuclear shuttling of YB-1 takes place. In this review, the clinical importance of YB-1 in different cancers and the mechanism behind YB-1 nuclear shuttling have been discussed in detail. Targeted chemotherapies or molecularly targeted drugs of great importance can target and block specific molecules implicated in tumor growth and progression. YB-1 has been considered as a bonafide oncogene and accumulating evidences show the therapeutic importance of YB-1. Therapeutic strategies targeting YB-1 may improve the survival rate in cancer patients. This review extensively discusses the therapeutic importance of YB-1.